Uniform convergence of the eigenfunction expansions associated with the bi-harmonic operator on the closed domain - Rakhimov, Abdumalik; Mohd Aslam, Siti Nor Aini (American Institute of Physics Inc., 2018)
In the paper we prove uniform convergence of the Riesz means of eigenfunction expansions associated with the bi-harmonic operator on the closed domain